2019
DOI: 10.1680/jwama.17.00079
|View full text |Cite
|
Sign up to set email alerts
|

Flow and longitudinal dispersion in channel with partly rigid floodplain vegetation

Abstract: The influence of rigid vegetation on the longitudinal dispersion coefficient in a compound open channel was examined using an image processing technique. To simulate floodplain vegetation, cylinders of 5 mm diameter were attached to the floodplain surface. Potassium permanganate solution was used as a conservative tracer. Instantaneous velocity components were measured using particle image velocimetry. The results showed that, compared with non-vegetated conditions, floodplain vegetation decreased the depth-av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The fact that the depth ratio weakens the impact of vegetation on the main channel flows and increases the velocity magnitude in the main channels may account for the negative correlation between the delay time and the relative depth. Specifically, both the velocity in main channels and floodplains increase with the increase in the relative depth, generating a larger x k , which is supported by several available studies [72][73]83] . In addition, the effects of canopies on the change of velocity in the main channel increase with the increase of r D , resulting in a larger incremental rate of x k compared with the compound channels without vegetation, where the lateral velocity variations are reduced by large relative depth.…”
Section: Influence Of Depth Ratio On the Longitudinal Dispersion Coef...supporting
confidence: 69%
See 1 more Smart Citation
“…The fact that the depth ratio weakens the impact of vegetation on the main channel flows and increases the velocity magnitude in the main channels may account for the negative correlation between the delay time and the relative depth. Specifically, both the velocity in main channels and floodplains increase with the increase in the relative depth, generating a larger x k , which is supported by several available studies [72][73]83] . In addition, the effects of canopies on the change of velocity in the main channel increase with the increase of r D , resulting in a larger incremental rate of x k compared with the compound channels without vegetation, where the lateral velocity variations are reduced by large relative depth.…”
Section: Influence Of Depth Ratio On the Longitudinal Dispersion Coef...supporting
confidence: 69%
“…[84], the longitudinal dispersion coefficient is reduced by the increase in the relative depth in the compound channels with vegetated floodplains, although the dispersion in the vegetated compound channels is also larger than that in the bare compound channels. The controversial results may be ascribed to the fact that the mean cross-sectional velocity in the study of Gu et al [84] decreased with the increase in r D , whereas the increase in the depth ratio leaded to the raise of mean velocity in other studies [72,83] . These results imply that the magnitude of mean velocity dominates the characteristics of dispersion within many influential factors, and has a positive relationship with the longitudinal dispersion coefficient.…”
Section: Influence Of Depth Ratio On the Longitudinal Dispersion Coef...mentioning
confidence: 86%
“…In each experiment, for a given flow, the corresponding flow depth was adjusted by a tailgate. More details about the experimental setup can be found in [54,55]. Each experiment lasted 6 h to reach semi-equilibrium conditions, following Melville and Chiew [51].…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the magnitude of LDC had an increasing trend by implanting vegetation over the floodplain as well as increasing the relative flow depth. Outcomes of two studies by Farzadkhoo et al 2018Farzadkhoo et al , 2019a indicated that roughening the floodplain with stems was one of the important factors in increasing the longitudinal flow velocity and the Reynolds shear stress in the main channel. The maximum value of nondimension (LDC/U ⁎ H) was also found at the bend apex.…”
Section: State Of the Artmentioning
confidence: 99%